Effectiveness of virtual classroom training in improving the knowledge and key maternal neonatal health skills of general nurse midwifery students in Bihar, India: A pre- and post-intervention study. (January 2016) - Agrawal, Neeraj; Kumar, Somesh; Balasubramaniam, Sudharsanam Manni; Bhargava, Saurabh; Sinha, Pallavi; Bakshi, Bhawna; Sood, Bulbul
Summary: Background: In 2008–09, the National Health Systems Resource Center of India reported overall quality of nurse-midwifery education in Bihar as grossly sub-optimal. To address this, we implemented a competency-based training using virtual classrooms in two general nurse midwives (GNM) schools of Bihar. The students from remotely located nursing institutions were now able to see live demonstrations of maternal and newborn health (MNH) practices performed by a trained faculty on simulation models at instructor location. Objective: To evaluate the effectiveness of virtual classroom training in improving the MNH-related skills of the nursing-midwifery students in Bihar, India. Design: This study used a pre- and post-intervention design without a control group. Settings: Students from two public GNM schools of Bihar. Participants: Final-year students from both the GNM schools who have completed their coursework in MNH. Method: A total of 83 students from selected GNM schools were assessed for their competencies in six key MNH practices using objective structured clinical examination method prior to intervention. A 72 hour standardized training package was then implemented in these schools through virtual classroom approach. Post-intervention, 92 students from the next batch who attended virtual training were assessed for the same competencies. Results: The mean student score assessed before the intervention was 21.3 (95% CI, 19.9–22.6), which increased to 62.0 (95% CI, 60.3–63.7) post-intervention. This difference was statistically significant. When adjusted for clustering using linear regression analysis, the students in post-intervention scored 52.3 (95% CI, 49.4%–55.3%) percentage points higher than pre-intervention, and this was statistically significant. Conclusion: Virtual classroom training was found to be effective in improving knowledge and key MNH skills of GNM students in Bihar, India. Highlights: Quality of nursing-midwifery education and training is suboptimal in Bihar. Students were trained in MNH skills through virtual classrooms. Pre–post evaluation was conducted to evaluate the effectiveness of training. Virtual platform was found effective in improving skills of nursing students.